2022
DOI: 10.1007/s13197-022-05570-6
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, antioxidant and sensory properties of Mango Sorbet containing L-theanine as a potential functional food product

Abstract: The non-proteinous amino acid L-theanine (L-THE) is associated with a range of health benefits including improvements in immune function, cardiovascular outcomes and cognition. The aims of this study were to develop a food product (mango sorbet; ms-L-THE) containing physiologically relevant doses of L-THE (0.2/100 g w/w) and determine its antioxidant, physicochemical and sensory properties in comparison to a mango sorbet without L-THE (ms). Total phenolic and flavanol content, and antioxidant analysis (DPPH, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In 2014, the Chinese State Food Safety Commission approved theanine as a novel food and stipulated that the daily intake of theanine should not exceed 400 mg. Therefore, based on its health benefits, theanine has been widely applied in foods (such as bakery food, , mango sorbet, and beverages) and dietary supplements . Moreover, theanine inhibited AGE formation in the bovine serum albumin-MGO model system and in rats, but its mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the Chinese State Food Safety Commission approved theanine as a novel food and stipulated that the daily intake of theanine should not exceed 400 mg. Therefore, based on its health benefits, theanine has been widely applied in foods (such as bakery food, , mango sorbet, and beverages) and dietary supplements . Moreover, theanine inhibited AGE formation in the bovine serum albumin-MGO model system and in rats, but its mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Passion fruit juice is characterized by an exotic flavor, but also by its significant content of nutrients, including phenolic compounds and ascorbic acid, as well as a lower sugar content [31][32][33][34][35]. Other studies have shown that mango and other exotic fruit sorbets are a good source of phenolic compounds, especially flavonoids [36][37][38].…”
Section: Introductionmentioning
confidence: 99%